2023
DOI: 10.1111/jce.15935
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial collision time (RACT): A novel marker of propensity for typical atrial flutter

Abstract: Introduction:The risk of typical atrial flutter (AFL) is increased proportionately to right atrial (RA) size or right atrial scarring that results in reduced conduction velocity. These characteristics result in propagation of a flutter wave by ensuring the macro re-entrant wave front does not meet its refractory tail. The time taken to traverse the circuit would take account of both of these characteristics and may provide a novel marker of propensity to develop AFL. Our goal was to investigate right atrial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This is understandable if one considers that MA size approximates PMAT circuit length, but offers no information about conduction time, including slow conduction, while E‐PMCT reflects both circuit length and conduction time. A recent study reported that conduction time around the tricuspid valve differed between patients with and without common AFL and could be used to determine whether to perform empirical ablation 27 . That study has many parallels to ours in that we use conduction time around the mitral annulus to predict PMAT.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This is understandable if one considers that MA size approximates PMAT circuit length, but offers no information about conduction time, including slow conduction, while E‐PMCT reflects both circuit length and conduction time. A recent study reported that conduction time around the tricuspid valve differed between patients with and without common AFL and could be used to determine whether to perform empirical ablation 27 . That study has many parallels to ours in that we use conduction time around the mitral annulus to predict PMAT.…”
Section: Discussionmentioning
confidence: 63%
“…A recent study reported that conduction time around the tricuspid valve differed between patients with and without common AFL and could be used to determine whether to perform empirical ablation. 27 That study has many parallels to ours in that we use conduction time around the mitral annulus to predict PMAT. However, it is significantly more difficult to create bidirectional block for the MI than for CTI, which makes weighing the decision whether or not to ablate more consequential.…”
Section: Mechanisms Of Pmat and Usefulness Of E-pmct For Estimation O...mentioning
confidence: 71%
“…Atrial conduction delay has been associated with atrial flutter and a marker of atrial electrophysiologic substrate and remodeling (Redfearn et al, 2006). Recent study demonstrated that patients with atrial flutter had significantly longer RA conduction time measured by right atrial collision time (RACT) during pacing from the coronary sinus than controls and patients who developed clinical AF later showed significantly longer RACT than those who did not among atrial flutter group (Ryckman et al, 2023). (Saini et al, 2017) and ultimately improve the intra-atrial conduction delay in our patient (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Journal, Rickman et al 1 take us into a new journey across the landscape of the cavo-tricuspid dependent atrial flutter (AFL) by enriching the old concepts with a novel parameter, i.e. right atrial collision time (RACT), whose role is to predict the occurrence of right common atrial flutter.…”
Section: Introductionmentioning
confidence: 99%
“…Rickman et al 1 have used this modality of pacing for investigating whether the collision time of the two wavefronts on the lateral wall of the right atrium could predict the occurrence of typical atrial flutter. For this purpose, the authors have designed a prospective study including a sample size of 98 patients, 41 having AFL and 57 as controls.…”
Section: Introductionmentioning
confidence: 99%